The Tectonics of China Data, Maps and Evolution - Wan, Tianfeng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
"The Tectonics of China: Data, Maps and Evolution" presents the regional geological and petroleum surveys of China, the author's original tectonic data, and research results of Chinese and international scientists (more than 1500 references) from the last three decades. It examines the main developments of geological evolution, a series of tectonic events in the overall geological history, 13 tectonic maps of the entire continent of Asia in different tectonic epochs, and a general discussion of the main tectonic characteristics of the Chinese continental plate. This book also intensively discusses the Mesozoic-Cenozoic tectonics and intraplate deformations, which control the majority of ore deposits and oil-gas reservoirs and have a tremendous influence on the climates and natural disasters on the continent. Some important tectonic theory problems are discussed, such as the mechanisms of the widespread intraplate deformation, the variation of lithosphere thickness, the existence of mantle plumes, the dynamic mechanisms for global tectonics, and the author's proposed hypotheses on mantle plumes and meteorite impacts. The book is intended for researchers and geologists working at universities, on geological surveys, for mining or petroleum companies, and for graduate students of geology and mineral resources. Tianfeng Wan is Professor at the China University of Geosciences, Beijing, China.
Research Principle and Method of Tectonics -- Tectonics of Archean and Paleoproterozoic (before 1.8 Ga) -- Tectonics of the Mesoproterozoic, Neoproterozoic and Early Cambrian (1.8 Ga - 513 Ma) -- Tectonics of Middle Cambrian - Early Devonian (The Qilian Tectonic Period, 513 - 397 Ma) -- Tectonics of Middle Devonian - Middle Permian (The Tianshan Tectonic Period, 397 - 260 Ma) -- Tectonics of Late Permian - Triassic (The Indosinian Tectonic Period, 260 - 200 Ma) -- Tectonics of Jurassic - Early stage of Early Cretaceous (The Yanshanian Tectonic Period, 200 - 135 Ma) -- Tectonics of Middle stage of Early Cretaceous - Paleocene (The Sichuanian Tectonic Period, 135 - 56 Ma) -- Tectonics of Eocene-Oligocene (The North Sinian Tectonic Period, 56 - 23 Ma) -- Tectonics of Miocene - Early Pleistocene (The Himalayan Tectonic Period, 23 - 0.78 Ma) -- Tectonics of Middle Pleistocene - Holocene (The Neotectonic Period, since 0.78 Ma) -- Characteristics and Mechanism of Chinese Continental Tectonics -- Tectonics and Thermal Regime of Chinese Continental Lithosphere -- Tectonics and Mineralization in China -- Discussion on the Dynamic Mechanism of Global Tectonics.-.
Keywords: Geography; Geology; Geology, Structural; Physical geography; Mineralogy; Earth Sciences; Structural Geology; Historical Geology; Geophysics/Geodesy.; Mineralogy